Proceedings of the Eighth Saudi Students Conference in the UK - Fréchet, Jean M. J.; Alford, Neil McN (Imperial College Press, 2016)
"This annual proceedings publishes peer-reviewed scholarly research conducted by postgraduate and early career researchers within the context of Saudi Arabia. It covers wide-ranging topics from diverse fields including humanities, social sciences and natural and applied sciences. The topics reflect the advancing knowledge, research trends, and scholarly debates across the entire spectrum of fields. The readership is broad and the topics appeal to both specialists and non-specialists. The contributions in the proceedings are thematised to reflect the cross-disciplinary nature of the conference. These are categorised as Medical and Health Sciences, Engineering and Applied Sciences, Natural Sciences, Law and Management Studies, Humanities and Social Sciences, and Arts"--Provided by publisher.